2017
DOI: 10.3389/fpls.2017.01674
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Seed Coats in Yellow-Seeded Brassica napus Reveals Novel Genes That Influence Proanthocyanidin Biosynthesis

Abstract: Yellow seeds are a favorable trait for Brassica crops breeding due to better quality than their black-seeded counterparts. Here, we compared the Brassica napus seed coat transcriptomes between yellow- and brown-seeded near-isogenic lines (Y-NIL and B-NIL) that were developed from the resynthesized yellow-seeded line No. 2127-17. A total of 4,974 differentially expressed genes (DEG) were identified during seed development, involving 3,128 up-regulated and 1,835 down-regulated genes in yellow seed coats. Phenylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 69 publications
7
67
3
Order By: Relevance
“…c and d). Recently, Hong et al () also observed the same phenomenon by chemical staining of developmental seeds in rapeseed, indicating the 21 DAF is an essential stage for seed coat coloration in rapeseed. Consistent with this finding, the expression level of BnTT8 showed a gradual increase during the early seed developmental stage and peaked at 23 DAF or 35 DAF (Fig.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…c and d). Recently, Hong et al () also observed the same phenomenon by chemical staining of developmental seeds in rapeseed, indicating the 21 DAF is an essential stage for seed coat coloration in rapeseed. Consistent with this finding, the expression level of BnTT8 showed a gradual increase during the early seed developmental stage and peaked at 23 DAF or 35 DAF (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Recently, two transcriptomic studies also found that these down‐regulated DEGs in yellow‐seeded coats were enriched in phenylpropanoid and flavonoid biosynthesis in resynthesized yellow‐seeded rapeseed as research materials (Hong et al , ; Jiang et al , ). Although the causal gene underlying the yellow‐seeded trait is still not clear in their materials, the two functional copies of BnTT8 were significantly down‐regulated in yellow seed compared with black seed in both cases (Hong et al , ; Jiang et al , ). It is reasonable to postulate that BnTT8 is involved in the down‐regulation of these DEGs in phenylpropanoid and flavonoid biosynthesis pathways directly or indirectly.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Removing these contaminants is a critical step, as RNA with high purity and integrity is critical for gene expression analyses. Although there are several methods available for seed RNA extraction (Kanai et al, 2017;Pereira et al, 2017;Mornkham et al, 2013;Suzuki et al, 2004); fewer protocols are available for the extraction of good quality RNA from specific seed tissue types, especially for the seed coat (Jiang et al, 2019;Liao et al, 2019;Hong et al, 2017;Kour et al, 2014).…”
Section: Introductionmentioning
confidence: 99%